دور القيادة الأخلاقية في الحد من دوافع وممارسات المحاسبة الإبداعية بالمنظمات (Economic studies journal, 2018)
The present study dealt with ethical leadership and creative accounting in a holistic framework to build an intellectual and field framework to determine the relationship between ethical leadership and creative accounting. The research problem is then addressed to what extent there can be a role for ethical leadership in reducing the motives and practices of creative accounting. The study of the importance of ethical leadership in reducing the motives and practices of creative accounting, from the point of view of faculty members Faculty of Economics and Accounting Merzk . And then distributed 44 questionnaires. The study found that ethical leadership has a significant role in reducing the motivation and practice of creative accounting by strengthening the transparency and ethics of professional business organizations
Keywords: القيادة; القيادة الأخلاقية المحاسبة; المحاسبة الإبداعية